Boredom : Documents of Contemporary Art. - McDonough, Tom; Blom, Ina; Bourriaud, Nicolas; Doyle, Jennifer; Efimova, Alla; Flatley, Jonathan; Foster Wallace, David; Haladyn, Jason; Katz, Jonathan, D.; Kraus, Chris; Lin, Tan; Lütticken, Sven; et al. (Londen : Whitechapel Gallery, 2017)
Akerman, Chantal ; Alÿs, Francis ; Baldessari, John ; Bernadette Corporation ; Brüggeman, Stefan ; Cage, John ; Critical Art Ensemble ; Cunningham, merce ; Duchamp, marcel ; Fontaine, Claire ; Higgins, Dick ; Johns, Jasper ; Judd, Donald ; Kabakov, Ilya ; Mikhailov, Boris ; Morris, Robert ; Pilson, John ; Polke, Sigmar ; Rainer, Yvonne ; rauschenberg, Robert ; Reinhardt ; Richter, Gerhard ; Situationist International ; Laderman Ukeles, Mierle ; Warhol, Andy ; Widing, Faith ; Zweig, Janet
modernity, industrialization, consumersim, punk, indifference, situationisme, alienation, personal intrusion
boek